2010
DOI: 10.1212/wnl.0b013e3181eee4d5
|View full text |Cite
|
Sign up to set email alerts
|

MYH7 gene tail mutation causing myopathic profiles beyond Laing distal myopathy

Abstract: The p.K1729del mutation in the MYH7 gene expresses notable clinical variability and electromyographic and pathologic features that can lead to the misdiagnosis of neurogenic atrophies, congenital myopathies, or mitochondrial myopathies. Mutations in genes encoding other sarcomeric and reticulo-sarcoplasmic proteins involved in calcium regulation share pathologic characteristics with our patients, suggesting a possible pathogenetic connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
100
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 34 publications
(36 reference statements)
15
100
3
Order By: Relevance
“…Several previous reports describe familial variability in MYH7-related myopathy [3,26,27]. Conversely, in our study, we observed rather homogeneous phenotype, albeit this of course cannot be applied to later onset forms, where younger patients present only a part of the full clinical spectrum.…”
Section: Myh7 Cases Have Interfamilial Variability and Less Intra-famcontrasting
confidence: 72%
“…Several previous reports describe familial variability in MYH7-related myopathy [3,26,27]. Conversely, in our study, we observed rather homogeneous phenotype, albeit this of course cannot be applied to later onset forms, where younger patients present only a part of the full clinical spectrum.…”
Section: Myh7 Cases Have Interfamilial Variability and Less Intra-famcontrasting
confidence: 72%
“…Dominant missense mutations in the b-myosin heavy-chain gene, MYH7, 29 may give rise to central cores on muscle biopsy with a distinct associated myopathy phenotype with or without cardiac impairment. 30 A cardiomyopathy associated with cores on muscle biopsy has also been documented in a mildly affected family harbouring dominant ACTA1 mutations 31 and severely affected siblings with homozygous truncating recessive titin mutations. 32 Central cores and multi-minicores as a secondary feature on muscle biopsy have been reported associated with mutations in the ACTA1, 33 DNM2 34 and NEB 35 genes, however, in most of these cases other findings, namely nemaline rods or centralised internal nuclei, are the most prominent histopathological feature.…”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 96%
“…Abundant examples can be found in neurology where a given gene has been associated with different clinical presentations, even within the same family [Ito, 2012;Nishioka et al, 2009]. Furthermore, often the diverse clinical profiles also reflect variability that can be demonstrated in the neurophysiologic and pathologic examination even in patients with the same mutation [Muelas et al, 2010]. Among recent discoveries further highlighting the variability of phenotypes that can be caused by a same mutation is the C9orf72 intronic expansion associated with motor neuron, extrapyramidal, cognitive, and psychiatric manifestations [Byrne et al, 2012;Simón-Sánchez et al, 2012].…”
Section: Challenges For Neurogenetic Databasesmentioning
confidence: 99%